Synthesis and characterization of wide bandgap semiconductors doped with terbium for electroluminescent devices - Montañez Huamán, Liz Margarita (2016)
In this work, stoichiometric, structural and light emission properties of amorphous wide bandgap semiconductor materials doped with terbium are presented. The amorphous nature of the thin films was confirmed by X-ray diffraction under grazing incidence. Fourier transform infrared spectroscopy spectra exhibit the formation of oxygen bonded elements and X-ray photoelectron spectroscopy reveals the formation of aluminum oxynitride and silicon oxycarbide as host matrices. The thin films were annealed at temperatures ranging from 300 °C to 1000 °C using a rapid thermal processing furnace. The highest light emission intensity for the case of aluminum oxynitride was obtained for terbium concentrations higher than 1 at% and for the annealing temperature at around 400 °C. Additionally, using the characterized films as active layer first electroluminescence devices were designed and investigated.